An Updated Systematic Review: The Distribution Dolphin Spinner (Stenella Longirostris) In Indian Ocean - Jannati Aulah; Indra Junaidi Zakaria; Nofrita (Institute of Computer Science (IOCS), 2022)
This study was conducted with the aim of summarizing papers related to the distribution of the Dolphin Spinner (Stenella longirostris) in the Indian Ocean waters that had been discovered previously. The focus of the papers is to examine the distribution of S. longirostris with survey method data collection techniques. The existence of S. longirostris in the Indian Ocean waters is characterized by low levels of predation. The appearance of S. longirostris in Indian Ocean waters is located around the shore which is rich food sources at a depth of 0 - 250m. The data obtained shows in which years the distribution points in the Indian Ocean. The results obtained indicate that S. longirostris appears in the Indian Ocean almost every year.